One-dimensional supramolecular hybrids: self-assembled nanofibrous materials based on a sugar gelator and calcite developed along an unusual axis. Issue 12 (24th February 2017) - Sukegawa, Haruka; Nishimura, Tatsuya; Yoshio, Masafumi; Kajiyama, Satoshi; Kato, Takashi
Abstract : One-dimensional nanohybrid structures based on calcium carbonate nanocrystals have been developed by using self-assembled fibrous templates of low-molecular-weight gelators. Abstract : One-dimensional (1D) supramolecular hybrid structures composed of self-assembled fibers and CaCO3 calcite crystals have been developed through an approach inspired by biomineralization. The supramolecular 1D template consisting of a low-molecular-weight gelator induces the crystal growth of calcite along an unusual axis.